Radioisotope gauges for industrial process measurements - Johansen, Geir Anton (John Wiley & Sons, 2004)
In order to fully utilise nucleonic measurement principles and their applications, it is important to have an understanding of the underlying physics. Radioisotope Gauges for Industrial Process Measurements combines theoretical background with practical experience in order to present an accessible overview of the use of radioisotopes in industry.